Revolutions and regimes of violence - Gallant, Thomas (Historein, 2016)
To study the phenomenon of revolution meaningfully in a cross-cultural context, scholars need frameworks of analysis that allow them to compare and contrast specific revolutions and to identify the factors that explain why certain sociopolitical systems are prone to rebellions and others are not. This article puts forth one such framework focusing on pre- and postrevolutionary violence. Revolution is a violent act and requires men and women who are ready, willing and able to perpetrate violence on behalf of a cause. The model proposes two ideal-type regimes of violence and suggests that some regimes are more violent-prone than others and that those regimes are also more susceptible to revolution. It suggests further that state-building after revolutions entails a process of reforming the regime of violence. The article ends by examining the case of Greece and the Ottoman empire over the long nineteenth century, showing how the models help us to better understand revolutionary and postrevolutionary regimes of violence.